The Increasing Role of Synergistic Effects in Carbon Mitigation and Air Quality Improvement, and Its Associated Health Benefits in China. (January 2023) - Wang, Jie; Lu, Xi; Du, Pengfei; Zheng, Haotian; Dong, Zhaoxin; Yin, Zihua; Xing, Jia; Wang, Shuxiao; Hao, Jiming
Abstract: A synergistic pathway is regarded as a critical measure for tackling the intertwined challenges of climate change and air pollution in China. However, there is as yet no indicator that can comprehensively reflect such synergistic effects; hence, existing studies lack a consistent framework for comparison. Here, we introduce a new synergistic indicator defined as the pollutant generation per gross domestic product (GDP) and adopt an integrated analysis framework by linking the logarithmic mean Divisia index (LMDI) method, response surface model (RSM), and global exposure mortality model (GEMM) to evaluate the synergistic effects of carbon mitigation on both air pollutant reduction and public health in China. The results show that synergistic effects played an increasingly important role in the emissions mitigation of SO2, NO x, and primary particulate matter with an aerodynamic diameter no greater than 2.5 μm (PM2.5 ), and the synergistic mitigation of pollutants respectively increase from 3.1, 1.4, and 0.3 Mt during the 11th Five-Year Plan (FYP) (2006–2010) to 5.6, 3.7, and 1.9 Mt during the 12th FYP (2011–2015). Against the non-control scenario, synergistic effects alone contributed to a 15% reduction in annual mean PM2.5 concentration, resulting in the prevention of 0.29 million (95% confidential interval: 0.28–0.30) PM2.5 -attributable excess deaths in 2015. Synergistic benefits to air quality improvement and public health were remarkable in the developed and population-dense eastern provinces and municipalities. With the processes of urbanization and carbon neutrality in the future, synergistic effects are expected to continue to increase. Realizing climate targets in advance in developed regions would concurrently bring strong synergistic effects to air quality and public health.